Joint Impact Assessment of CTA's support to CARDI (2003-2013) - Glean, Allister; Maximay, Steve (Technical Centre for Agricultural and Rural Cooperation, 2020)
This In-depth assessment of the impact of CTA funding, through joint initiatives with CARDI, is the culmination of a three-phased undertaking. The in-depth assessment results coincide significantly with the findings of the first two phases of the Capacity Centered Impact Pathway Analysis (CcIPA). The impacts documented herein are reinforced by the use of embedded quick response codes that link to the “proof” of impact whether such impact is in changed perception, improved operations or personal/institutional development.